2009
DOI: 10.3390/su1020277
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biosorbents from Waste Olive Cake and Its Adsorption Characteristics for Zn2+ Ion

Abstract: In this study, waste olive cake (OC) was utilized as the raw material for the production of biosorbents by chemical treatment and its adsorption capacity for zinc ion was evaluated. Tests were conducted with the total biomass (T) and with the fraction > 2.00 mm (P), in order to determinate the influence of this fractionation step on subsequent treatments. Two chemical agents were used: sulfuric acid and sodium hydroxide. The parameters studied include physical and chemical properties of materials, contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 55 publications
1
27
0
1
Order By: Relevance
“…The removal of Zn 2? from effluents is a major problem due to the difficulty in treating such wastewaters by conventional treatment methods (Fernando et al 2009). Hence, substantial research is currently under progress to find suitable, highefficiency and low-cost natural sorbents for Zn 2?…”
Section: Zincmentioning
confidence: 99%
“…The removal of Zn 2? from effluents is a major problem due to the difficulty in treating such wastewaters by conventional treatment methods (Fernando et al 2009). Hence, substantial research is currently under progress to find suitable, highefficiency and low-cost natural sorbents for Zn 2?…”
Section: Zincmentioning
confidence: 99%
“…This technology is based on the capacity of many biological materials to bind and remove heavy metals from aqueous effluents (Vieira and Volesky 2000;Volesky 2001). It employs the use of various divergent biomass, such as algae (Rathinam et al 2010), seaweeds (Baral et al 2008), bacteria (Wang et al 2010), fungi (Ahluwalia and Goyal 2010), agrowastes including husk (Boucher et al 2008), fibers (Makehelwala et al 2009), sawdust (Ting et al 2010), tea waste (Prabhakaran, Vijayaraghavan, and Balasubramanian 2009), bagassae (Samadi et al 2009), seed cake (Boucher et al 2008;Fernando et al 2009), etc. Seed cakes are the secondary by-product generated after the oil extraction from oleaginous seeds, which are poorly utilized.…”
Section: Introductionmentioning
confidence: 99%
“…37 The removal of Zn 21 from effluents is a major problem due to the difficulty in treating such wastewaters by conventional treatment methods. 37,67,68 Biosorption could be the appropriate alternative and several studies reported in the literature for the removal of this metal support the feasibility of this removal technique. 67,68…”
Section: Zincmentioning
confidence: 92%